Relative validity of a food frequency questionnaire in patients coinfected with hepatitis C virus and human immunodeficiency virus - Anelise Fernanda Zanolla; Caroline Buss; Dimas Alexandre Kliemann; Giselle Souza Pinto; Vivian Silveira Vasques; Cristiane Valle Tovo (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT INTRODUCTION: Validation of food frequency questionnaires (FFQs) is recommended for accurate measurement of habitual food consumption. We assessed the relative validity of a FFQ in patients coinfected with hepatitis C virus and human immunodeficiency virus. METHODS: Each patient responded to a FFQ and three 24-hour food recalls. Pearson’s correlation and weighted Kappa index analyses were performed to identify the FFQ relative validity and concordance. RESULTS: De-attenuated correlation coefficients ranged from 0.35 (vitamin B1) to 0.81 (selenium). The concordance index ranged from 0.07 (vitamin C) to 0.51 (calcium). CONCLUSIONS: The FFQ showed satisfactory relative validity for most nutrients.